Remembering Zygmunt Bauman (1925-2017) - Silva, Filipe Carreira da (2017)
At the time of his death, 9 January 2017, Zygmunt Bauman was one of the foremost social theorists in the world. During an academic career spanning seven decades and several countries, Bauman published relentlessly (more than 50 books) and won several international awards. He was consensually recognised as a commanding voice in debates on ethics, globalisation, modernity, consumerism, and lately on the rise of populism. Although his thinking evolved signi cantly over time, his writings express a continued preoccupation with the moral vagaries of our time and, in particular, with the su ering of the dispossessed and the excluded. As he writes in Globalization: e Human Consequences: “If you de ne your value by the things you acquire and surround yourself with, being excluded is humiliat- ing.” is insight, according to which exclusion is the ipside of the promises and realities of democratic inclusion, a contradiction at the heart of the mod- ern condition, is perhaps the central and most enduring feature of Bauman’s thinking.